Entwurf und Modellierung von Breitbandverstärkern mit variablem Gewinn in SiGe BiCMOS Technologien - Vangerow, Christian von (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2019)
The present work deals with the development of broadband amplifiers with adjustable gain. Different circuit topologies for gain control are investigated, and several compact and distributed amplifiers are fabricated in SiGe BiCMOS technologies. Another key aspect of the work is the modeling of distributed amplifiers by means of image parameters, which enable an analytical and compact description.